Transition to Motherhood and Lived Experiences of Teenage Mothers Delivering in Kasese and Bundibugyo Districts, Western Uganda - Ngonzi, Joseph; Ainomugisha, Brenda; Byamukama, Onesmus; Tumuhimbise, Wilson; Asiimwe, Josephine; Kamugisha, Arnold; Ntaro, Moses; Nambozi, Grace; Bebell, Lisa (Cureus, 2024)
Introduction: A large number of teenagers in low-resource settings experience pregnancy, with a significant number of these cases happening in sub-Saharan Africa. Teenage pregnancy is associated with unique physical and psychological experiences. Objective: To explore the lived experiences of teenage mothers delivering at a tertiary referral hospital in southwestern Uganda. Methods: This qualitative study used focus group discussions (FGDs) with teenage mothers in Kasese and Bundibugyo districts in Uganda. We purposively sampled 32 teenage mothers attending a tertiary referral hospital who had been pregnant at least once and had given birth. Sociodemographic information was obtained, and FGDs were conducted to capture the teenagers’ experiences transitioning to motherhood. An inductive content analytic approach was used to analyze data. Results: The mean age of the participants was 18.4 (standard deviation [SD], 1.2) years, with the majority (22, 68.8%) being rural dwellers, married (23, 71.9%), unemployed (21, 65.6%), and having attained primary education (23, 71.9%). Teenage mothers’ lived experiences were characterized by shattered dreams, concerns about changes in their body size and shape, abandonment and neglect by family members and spouses, considerations of terminating the pregnancy, forced early marriages, family stereotypes, and engaging in sex for survival. The process of transitioning to motherhood occurred along with resilience post-pregnancy and supportive environments from their loved ones, which enabled them to accept reality and care for their children. Conclusions: The lived experiences of teenage mothers demonstrated social pressures, fear of abandonment, and poverty as major influences on their mindset and behavior. Further research to gain a comprehensive understanding of the challenges encountered by teenage mothers will aid the development of culturally appropriate strategies to reduce teenage pregnancy and improve perinatal outcomes.
Keywords: Uganda; Transition to motherhood; Lived experiences; Maternal child; Teenage pregnancy